2012
DOI: 10.1590/s1516-35982012000900007
|View full text |Cite
|
Sign up to set email alerts
|

Follicular dynamics and production of oocytes in young Nellore heifers with energetic supplementation

Abstract: -To verify the effects of energy supplementation and fat on follicular dynamics, metabolic profile and the production of oocytes, 15 young heifers (Bos taurus indicus) with an average age of 14 months and with an initial weight of 256.35 kg were assigned to two treatments according to weight and follicular population as evaluated by ultrasonography: in T1 (1.0 × M), animals received 100% of the energy requirements for maintenance; in T2 (1.7 × M), animals received 170% of the energy requirements for maintenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 31 publications
3
9
1
3
Order By: Relevance
“…In general, a high level of urea decreases the number of viable follicles and reduces the fertility of ruminants (Leroy et al., ; Ferreira et al., ; Ying et al., ). In contrast, other authors have associated the inclusion of fat in the ruminant diet with an increased cholesterol concentration in the plasma (Grummer and Carroll, ; Nogueira et al., ). These effects were not observed in the present study, because the prepubertal goats did not present a negative energy balance, and the inclusion of soya bean oil did not increase urea and cholesterol levels.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In general, a high level of urea decreases the number of viable follicles and reduces the fertility of ruminants (Leroy et al., ; Ferreira et al., ; Ying et al., ). In contrast, other authors have associated the inclusion of fat in the ruminant diet with an increased cholesterol concentration in the plasma (Grummer and Carroll, ; Nogueira et al., ). These effects were not observed in the present study, because the prepubertal goats did not present a negative energy balance, and the inclusion of soya bean oil did not increase urea and cholesterol levels.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the inclusion of fat in the diet of heifers results in a significant increase in the synthesis of steroid hormones (Butler et al., ; Mattos et al., ; Nogueira et al., ), and the inclusion of 3% soya bean oil in the diet of heifers is sufficient to induce puberty (Whitney et al., ; Fouladi‐Nashta et al., ). Similarly, the inclusion of soya bean oil in the diet of prepubertal goats may be used as a management strategy to accelerate puberty and increase the reproductive efficiency of the herd (Whitney et al., ; Ying et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…After seven OPU sessions, no difference was observed in AFC among sessions of cows supplemented or not supplemented with linseed. The effects of the addition of PUFAs in the diet of cattle on AFC are quite controversial, and studies showing positive effects or no effect can be found (BILBY et al, 2006;FOULADI-NASHTA et al, 2009;PONTER et al, 2012;NOGUEIRA et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Diets rich in linoleic acid, similar to that present in linseed, or with the addition of soybean oil to their formulations increase hepatic gluconeogenesis owing to the increase of rumen propionate production (THOMAS;WILLIAMS, 1996). The increase in gluconeogenesis has been associated with elevations in plasma concentrations of insulin and IGF-1, which are capable of increasing the number of small and medium follicles in Nelore heifers (NOGUEIRA et al, 2012). On the contrary, Bilby et al (2006) found that supplementing dairy cows with mono and polyunsaturated fatty acids did not lead to a difference in the number of follicles present in the ovaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation